2014
DOI: 10.1051/e3sconf/20140301020
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Work Adjustment of Malaysian Expatriate Executives in Malaysian Construction Companies Overseas

Abstract: Abstract. The development of Malaysia's economy gives the opportunities for companies to explore and operate overseas. A company has to ensure that the selected individuals are willing to work abroad, have high perseverance and always ready to meet challenges. The success of implementing the overseas assignment does not solely depend on technical expertise. It also depends on non-technical issues such as the ability to interact with colleagues at work, adaptability to the new environment and openness to the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Also, it has been mentioned in the literature that the success of implementing overseas assignment does not solely depend on technical expertise; there are non-technical issues involved too such as culture, family, work procedures, and ability to interact with colleagues at work, adaptability and openness to local culture all exert influence on the assignment committed to these expatriates. In the work by (H. Zainol et al, 2014), using factor analysis, the findings of the study found the factors that loaded on work adjustment of expatriates, task satisfaction in the new post was the most important factor that influenced work adjustment and overall performance at the new job. The other factor that loaded significantly on work adjustment for the expatriate is the reward.…”
Section: Review Of Related Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…Also, it has been mentioned in the literature that the success of implementing overseas assignment does not solely depend on technical expertise; there are non-technical issues involved too such as culture, family, work procedures, and ability to interact with colleagues at work, adaptability and openness to local culture all exert influence on the assignment committed to these expatriates. In the work by (H. Zainol et al, 2014), using factor analysis, the findings of the study found the factors that loaded on work adjustment of expatriates, task satisfaction in the new post was the most important factor that influenced work adjustment and overall performance at the new job. The other factor that loaded significantly on work adjustment for the expatriate is the reward.…”
Section: Review Of Related Literaturementioning
confidence: 96%
“…In several organizations (Merry, 2013) this expatriate adjustment has been abstracted as the extent of adjustment, experienced by the individual or the level of comfort, familiarity, and ease that the individual feels toward the new environment (Gupta and Gupta, 2012). Such ability for an expatriate to work in a new environment depends on adaptation and adjustment in new surroundings, relatives' effect, the facility to communicate with a workmate and being open to the new community (Zainol et al, 2014). The non-family duty stations are duty stations classified by the International Civil Service Commission (ICSC) as when the United Nations Department for Safety and Security (UNDSS) decides that eligible respondents of expatriate workers are restricted from being present at the duty station for six months or longer most times (UNOPS, 2016) usually because it is too dangerous for the immediate families to stay.…”
Section: Introductionmentioning
confidence: 99%